Novel insights into pathophysiology and therapeutic possibilities reveal further differences between AQP4-IgG- and MOG-IgG-associated diseases. Issue 3 (June 2020) - Mader, Simone; Kümpfel, Tania; Meinl, Edgar
Abstract : Purpose of review: This review summarizes recent insights into the pathogenesis and therapeutic options for patients with MOG- or AQP4-antibodies. Recent findings: Although AQP4-IgG are linked to NMOSD, MOG-IgG-associated diseases (MOGAD) include a broader clinical spectrum of autoimmune diseases of the central nervous system (CNS). Details of membrane assembly of AQP4-IgG required for complement activation have been uncovered. Affinity-purified MOG-IgG from patients were shown to be pathogenic by induction of demyelination when the blood–brain barrier (BBB) was breached and by enhancement of activation of cognate T cells. A high-affinity AQP4-IgG, given peripherally, could induce NMOSD-like lesions in rats in the absence of BBB breach. Circulating AQP4-specific and MOG-specific B cells were identified and suggest differences in origin of MOG-antibodies or AQP4-antibodies. Patients with MOG-IgG show a dichotomy concerning circulating MOG-specific B cells; whether this is related to differences in clinical response of anti-CD20 therapy remains to be analyzed. Clinical trials of AQP4-IgG-positive NMOSD patients showed success with eculizumab (preventing cleavage of complement factor C5, thereby blocking formation of chemotactic C5a and membrane attack complex C9neo), inebilizumab (depleting CD19 + B cells), and satralizumab (anti-IL-6R blocking IL-6 actions). Summary: New insights into pathological mechanisms and therapeutic responses argue to consider NMOSD with AQP4-IgG and MOGAD as separate disease entities.